Primeiro registro de predação de Poecilia reticulata Peters, 1859 e Phalloceros caudimaculatus (Hensel, 1868) por Noctilio leporinus (Linnaeus, 1758) (Chiroptera, Noctilionidae) - Breviglieri, Crasso Paulo B.; Pedro, Wagner Andre (My University, 2008)
Noctilio leporinus (Chiroptera, Noctilionidae) has adaptations to piscivorous feeding habits, but also consumes crustaceans and insects. Between June 2005 and May 2006, bats were surveyed with mist nets during two evenings per month in the gallery forest of Corrego dos Tenentes, Pindorama, São Paulo State, Brazil. The objectives were to collect fecal samples and identify the fish species that were consumed by N. leporinus in this fragmented forest landscape. We documented two new fish species to its diet, the guppy Poecilia reticulata, Peters, 1859 and the "guaru" Phalloceros caudimaculatus (Hensel, 1868). Both fish species forage near the surface of water for insects and zooplankton, which is an area also utilized by N. leporinus when foraging for insects, crustaceans and fishs.
First record of predation on Poecilia reticulata Peters, 1859 and Phalloceros caudimaculatus (Hensel, 1868) by Noctilio leporinus (Linnaeus, 1758).